External Disruption Following CEO Succession: How Human and Social Capital Changes May Attract Competitive Attacks - Lee, Eric Y.; Tsai, Wenpin (Academy of Management Journal, 2024)
Competitors may perceive a focal firm’s CEO succession as creating an exploitable opportunity as well as a future threat to preempt. Drawing from theories of executive human and social capital, we suggest that anticipation of internal disruption stemming from human and social capital changes in a CEO succession may lead to external disruption for the focal firm. In our sample of S&P 500 firms between 2010 and 2018, we find that competitors are more likely to attack the focal firm when the successor’s professional experience differs drastically from that of the predecessor and less likely to do so when the successor is an insider. We also find that competitors’ attacks following a succession event can be minimized by limiting changes to only one form of capital (i.e., human or social). Moreover, retaining the predecessor as board chair after the succession could be an effective human capital preservation strategy for reducing competitors’ attacks when the difference in professional experience between the predecessor and successor is high. However, retaining the predecessor as board chair may not have the same effect when it comes to social capital. Our research highlights the competitive implications of CEO succession, offering new insight into disruption.